The effect of dalteparin on coagulation activation during pregnancy in women with thrombophilia - Abou-Nassar, Karim; Kovacs, Michael J.; Kahn, Susan R.; Wells, Philip; Doucette, Steve; Ramsay, Tim; Clement, Anne Marie; Khurana, Rshmi; MacKinnon, Karen; Blostein, Mark; Solymoss, Susan; Kingdom, John; Sermer, Matthew; Rey, Evelyne; Rodger, Marc; the TIPPS investigators (Thrombosis and Haemostasis, 2007)
Low-molecular-weight heparin (LMWH) is increasingly being used for prophylaxis of venous thromboembolism (VTE) and prevention of pregnancy associated morbidity in pregnant women with thrombophilia. We sought to determine if the administration of prophylactic doses of LMWH downregulates coagulation activation in high risk pregnant women with thrombophilia. This sub-study was planned as part of a randomized open label controlled trial (Thrombophilia in Pregnancy Prophylaxis Study[TIPPS])in which patients at high risk of pregnancy complications with confirmed thrombophilia are randomized to receive either dalteparin (5,000 units/day until 20 weeks then 5,000 units q12h until 37 weeks or onset of labor) or no treatment. Blood samples were collected at baseline, day 7–9 (after starting study drug), week 20 (before increasing study drug), week 36 (prior to stopping study drug) and at the time of admission to the labor and delivery unit. Samples were not drawn at fixed times in relation to drug injection. These samples were analyzed for levels of thrombin-antithrombin complexes (TAT), prothrombin fragments 1+2 (F1.2), D-dimer and anti-Xa activity. Generalized linear mixed models were used for statistical analysis and model results were controlled for age, smoking status, type of thrombophilia and predisposing risk factors. The effect of dalteparin onTAT levels was defined as the primary outcome. Of 198 patients eligible, 114 were enrolled in TIPPS. Ninety-one were eligible for the TIPPS coagulation activation sub-study and randomized. Thirty-nine patients were analyzed in the treatment group (dalteparin) and 46 patients in the control group (no intervention). Levels of coagulation activation factors F1.2, TAT and D-dimer increased significantly throughout pregnancy in both groups (p<0.0001). Dalteparin prophylaxis resulted in a significant increase in anti-Xa activity through pregnancy (p<0.0001) compared to controls. Dalteparin had no significant effects on the levels of TAT, F1.2 and D-dimer throughout pregnancy in thrombophilic women.A post-hoc Monte Carlo power analysis revealed that our study had 100% and 88% power to detect reductions in TAT values on treatment of 50% and 25%, respectively. Prophylaxis with dalteparin at doses used in this study did not reduce coagulation activation in high risk thrombophilic women during pregnancy.
Keywords: Low-molecular-weight heparin; pregnancy; thrombophilia; coagulation activation